LEGAL RECONSTRUCTION OF PUBLIC HEALTH SERVICE PROGRAMS ON TELEVISION BROADCASTING INSTITUTIONS - Riyanto, Mochamad (UNTAG Law Review, 2019)
The writing of this paper analyzes the legal position contained in the Law relating to public health broadcast programs. Further review of the legal aspects of public health broadcast programs that researchers do are not limited to understanding the legal construction that applies in the positivism perspective, but researchers conduct legal reconstruction of public health broadcast programs on television broadcasting institutions with a post-positivism perspective approach namely conceptualizing the law as a set of rules of enactment are influenced by economic, political and social cultural factors. Then there is a need for regulative efforts in the context of the spectrum of balancing laws relating to market regulation and state regulation. The results of the discussion found the following conclusions: First, there was no harmonization in the legal spectrum relating to public health service broadcast programs on television which were dominated in the form of promotions, commercial advertisements, and publications relating to drugs. Second, the laws and regulations governing public health service broadcast programs in broadcasting institutions have not encouraged strong public awareness about the highest degree of health. Third, the public health service broadcast program has a social impact on the interests of the community that is in the form of community self-awareness but also has an economic impact especially for the drug industry and hospitals. However in regulative, it has not provided a framework for social and economic impacts.